2017
DOI: 10.1038/s41598-017-00833-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of C3 gene with uveitis: additional insights into the genetic profile of uveitis regarding complement pathway genes

Abstract: Uveitis is a devastating ocular disease that causes blindness. Our previous studies have achieved great advancements in depicting the genetic profiles of uveitis regarding complement pathway genes. This study aimed to provide additional insights into this interest by testing the "central" factor of the complement system, C3 gene variants, in two uveitis entities. Eight haplotype-tagging SNPs of C3 gene were genotyped in 141 anterior uveitis (AU), 158 non-infectious intermediate and posterior uveitis (NIPU) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Of them, variants in the CFH, CFB and CFI involved in the alternative pathway, were identified as genetic risk markers for various uveitis subtypes [16][17][18][19][20]. A recent report from our laboratory also demonstrated that the classical pathway gene, C1INH, as well as the central component of the cascade, C3 gene, may confer either no or limited risk for uveitis susceptibility [21,22]. Overall, our findings together suggest that the alternative pathway as well as the "upstream" cascade of complement system confers major genetic impact on uveitis susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of them, variants in the CFH, CFB and CFI involved in the alternative pathway, were identified as genetic risk markers for various uveitis subtypes [16][17][18][19][20]. A recent report from our laboratory also demonstrated that the classical pathway gene, C1INH, as well as the central component of the cascade, C3 gene, may confer either no or limited risk for uveitis susceptibility [21,22]. Overall, our findings together suggest that the alternative pathway as well as the "upstream" cascade of complement system confers major genetic impact on uveitis susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…The genotypes were read by the system software (Prism 7000 SDS software version 1.1; ABI). More details were described in our previous studies [20,22].…”
Section: Single Nucleotide Polymorphism Selection and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such associations were not found for the interleukin-23 receptor single-nucleotide polymorphisms (SNPs) reported in other autoimmune diseases [43]. Complement C3 SNPs also lacked an association with non-infectious intermediate and posterior uveitis [44], although polymorphisms in the Complement Factor H gene implicated in age-related macular degeneration were statistically increased compared to controls in patients with intermediate uveitis [45]. Interplay between cytokine polymorphisms was proposed to alter prognosis in intermediate uveitis [46].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…The complement system, a key innate immune defense system, plays an important role in modulating various immune and inflammatory responses. In our previous studies, we intensively studied the genetic profiles of complement pathway genes in uveitis, including complement factor H (CFH), complement factor B (CFB), complement component 2 (C2), complement component 3 (C3), complement component 5 (C5), and complement component 1 inhibitor gene (SERPING1) (9)(10)(11)(12)(13)(14)(15)(16)(17). Moreover, recent studies have implicated complement cascades in glaucomatous neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%